The politics of chemistry : science and power in twentieth-century Spain - Nieto-Galan, Agustí (Science in history (Cambridge University Press), 2019)
Nieto-Galan examines the political role of chemistry in twentieth-century Spain, enriching understandings of the relationship between science and power.